The role of triangulation in sensitive art-based research with children. (2nd May 2017) - Vanner, Catherine; Kimani, Mary
Abstract : Purpose: The purpose of this paper is to highlight the critical role of triangulation to create authentic analytical frameworks amidst contradictory participant narratives in sensitive art-based research (ABR) with children. Design/methodology/approach: Multiple qualitative case study research included three months of participant observation, individual semi-structured teacher interviews and open-ended art-based interviews using the Draw-Write-Narrate method (Ogina and Nieuwenhuis, 2010) with upper primary students in two schools in Kirinyaga County, Kenya. Findings: The art-based approach to student interviews, combined with participant observation and teacher interviews, provided a child-centred process that illuminated students' understandings and experiences while minimizing risks to participants. Its application requires researchers to recognize data collection and analysis as subjective processes that strongly benefit from triangulation to interpret a diversity of perspectives that may not easily align. Originality/value: As ABR with children increases in popularity, it is important to identify challenges in the process of analysis and meaning-making. This paper identifies triangulation as a valuable tool for handling the challenge of diverse perspectives from child participants, particularly in conducting sensitive research that may increase the likelihood of contradictory narratives.